Early Chinese Settlements Adaptive Reuse as History and Activity Node at Lasem Living Museum - Ardelia J. Cungwin; Widjaja Martokusumo (Journal of Infrastructure & Facility Asset Management, 2021)
The concept of a living museum depicts Lasem – a multi-ethnic city known for its harmonious community – as a small city with diverse heritage nodes spreading across its plateau. However, the first settlements that became the prologue of Lasem’s history and development, are not being appreciated enough as it is now being used for swallow's nest production. Therefore, it is necessary to do a thoughtful conservation effort for the area of the early settlements, as one of the important nodes in Lasem. The reuse of heritage buildings and reactivation of the area into a place of activity that can support economic activities, social needs, and cultural sustainability for the people, will create more sustainable tourism for Lasem as an integrated living museum. Batik Tiga Negeri is Lasem’s distinctive fabric product and intangible heritage with an international reputation. The handmade creation involves endangered heritage: the elderly artists and the traditional Chinese architecture-influenced building which is used as the production house. Merging batik value into the adaptive reuse of early settlement buildings – which is also derived from traditional Chinese housing, will strengthen the most historical node while conserving important heritage elements, adding stronger bonds throughout Lasem as both a living museum and tourism destination.